(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
The purpose of this article is to present some values of family socialization of children in a local community, the Mozabite community of Ghardaïa. The main question is whether this socialization is based on a community value system or a societal value system. Referring to a theoretical framework of the German sociologist Ferdinand TÖNNIES and based on field investigations in Ghardaïa, we present in this article some values related to collective memory, the domestic living environment and the socialization of children proper. Finally, we end with questions related to the problem of social change applied to this case of the Mozabite community. KEYWORDS- Mzab, community, family, values, socialization.